Foliões do quilombo Carrazedo: Catolicismo popular, hierofania e seus instrumentos sagrados - Santos, Fábio José Brito dos (Numen, 2025)
The revelers of São José are percussionists who make up the largest quilombola manifestation in the municipality of Gurupá - Pará. This article is the result of a master's dissertation linked to the State University of Pará - UEPA, and aims to understand the revelers of São José of the Carrazedo quilombo and their sacred instruments from a hierophant and popular devotion perspective. The methods used were participant observation, semi-structured interviews and theoretical support to support the analyses. The results conceived a riverside and promesseiro profile of the percussionists in a system of compadrio, the Afro-indigenous and European influence in the elements that make up the folia, such as: the presence of elements that resemble other popular Amazonian manifestations, the frequency of concepts that allude to indigenous ancestry, the African diaspora in the region and the strong repression of the Catholic Church in the defense of canonical precepts.